Application of Business Rights Over Management Rights Based On Government Regulation No. 18 of 2021 - Isnin Harianti; Astari Cahyaningtyas Winantyo; Ananda Amalia Tasya (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
The purpose of this study is to review the application of regulations on The Right to Business regulated in P emerintah Regulation No. 18 of 2021 on Management Rights, Land Rights, Flats Units, and Land Registration. After the enactment of this regulation, all other implementing regulations were revoked and declared invalid. In fact, this implementing rule is contrary to the law on it, namely Law No. 5 of 1960 on the Basic Rules of Agrarian Trees. One of the conflicting rules related to the Right to Business regulations stipulated in Law No. 5 of 1960 on Basic Rules of Agrarian Principals, that The Right to Business can only stand on state land, regulated differently in its implementing regulations, namely in the Regulation of Pemerintah No. 18 of 2021, which states that The Right to Business can stand on the land of Management Rights. So that not only the clash of rules but also contrary to the principle of legal preferences. So that the existence of this rule even though legal fiction has been applied still causes controversy and debate in the world of academics and practitioners. This legal research research method uses statute approach and conceptual approach to analyze two legal issues, namely the regulationof Hak Guna Usaha on land Hak Pengelolaan in the laws and regulations in Indonesia and the problem of applying the rules Hak Guna Usaha on land Hak Pengelolaan. The result of this study is that due to the conflict of legal preference principle related to implementing regulations with laws on it, until now, The Right to Business can only be granted on State Land, not above Management Rights.